#TITLE_ALTERNATIVE# - Setiadbudy NIM : 22397017, Inderawati
Abstract: Most geophysical media is anisotropy. A media is defined as anisotropy when its physical properties depend on direction. Leon Thomsen derived formula to determine weak elastic anisotropy parameters, namely, e, S, and y. Using three-component seismic data corrected with the polarization shear wave correction, the weak anisotropy parameters will be determined based on normal moveout veloci of compressional wave and shear wave of Leon Thoms en. The aim of this research is to determine the weak anisotropy parameters, particularly on shear wave and is applied on a real data. So far, research on anisotropy parameter in Indonesia stressed on compressional wave. Observation are made on points with equal CDP which indicate geological characteristic (based on interpretation result ..., on stacked seismic). The final results are weak elastic anisotropy parameters which values are varied, and some observation points satisfying weak anisotropy theorem. Some observation points do not satisfy weak anisotropy theorem, because offault, fluid or tectonic.